Flavoprotein monooxygenases for oxidative biocatalysis: recombinant expression in microbial hosts and applications - Ceccoli, Romina D.; Bianchi, Dario A.; Rial, Daniela V. (Frontiers in Microbiology, 2014)
External flavoprotein monooxygenases comprise a group of flavin-dependent oxidoreductases that catalyze the insertion of one atom of molecular oxygen into an organic substrate and the second atom is reduced to water. These enzymes are involved in a great number of metabolic pathways both in prokaryotes and eukaryotes. Flavoprotein monooxygenases have attracted the attention of researchers for several decades and the advent of recombinant DNA technology caused a great progress in the field. These enzymes are subjected to detailed biochemical and structural characterization and some of them are also regarded as appealing oxidative biocatalysts for the production of fine chemicals and valuable intermediates toward active pharmaceutical ingredients due to their high chemo-, stereo- and regioselectivity. Here, we review the most representative reactions catalyzed both in vivo and in vitro by prototype flavoprotein monooxygenases, highlighting the strategies employed to produce them recombinantly, to enhance the yield of soluble proteins, and to improve cofactor regeneration in order to obtain versatile biocatalysts. Although we describe the most outstanding features of flavoprotein monooxygenases, we mainly focus on enzymes that were cloned, expressed and used for biocatalysis during the last years.